A new record of the genus Parabioxys (Hymenoptera, Braconidae, Aphidiinae) and a redescription of Bioxys japonicus from South Korea - Sangjin Kim; JuHyeong Sohn; Yerim Lee; Yeonghyeok Yu; Hyojoong Kim (Journal of Hymenoptera Research)
The genera Bioxys Starý & Schlinger, 1967 and Parabioxys Shi & Chen, 2001 (Hymenoptera: Braconidae: Aphidiinae) are each known to contain only one species worldwide. Bioxys japonicus Starý & Schlinger, 1967 was recorded in South Korea in 1983, but this record should be considered doubtful. Parabioxys songbaiensis Shi & Chen, 2001 is now reported for the first time in South Korea. In this study, we provide detailed descriptions and photographic documentation of these two little-known species, B. japonicus and P. songbaiensis. Additionally, we present mitochondrial cytochrome c oxidase subunit I (COI) barcode region data and conduct a Bayesian tree analysis of closely related taxa.